WAYS OF THINKING SISWA SEKOLAH MENENGAH ATAS DALAM PEMECAHAN MASALAH KONTEKSTUAL MATEMATIS PADA MATERI FUNGSI EKSPONEN - Fauziah Fakhrunisa, - (2021)
This study aims to obtain a comprehensive description of the tendency of high school students' ways of thinking which consists of problem-solving approaches and beliefs about mathematics in solving applied mathematical problems. Qualitative research methods with a phenomenological approach are used to answer the research questions. As an effect of the COVID-19 pandemic, all stages were carried out online with the assisstance of WhatsApp,, gmail, and google form. Then, the data obtained using the written test method which consists of five applied mathematical problems and a questionnaire about beliefs about mathematics. In addition, semi-structured interviews were also chosen as the data interview method. There are 24 students at class X, from one of the state high schools in West Java Province, that willing to be the participant of this study. Based on the analysis of the findings, it can be concluded that the students' problem-solving approach in solving applied mathematical problems related to understanding competencies tends to vary according to their level of cognitive ability, the same thing happens to students' problem-solving approaches to applied mathematical problems related to mathematizing competences and working mathematically. Meanwhile, students' problem-solving approach in solving applied mathematical problems related to interpreting and validating competencies shown by moderate kognitif ability (KKS) and low cognitive ability (KKR) students tends to be the same. In addition, this study also analyzes the students' belief about mathematics category by giving a questionnaire consisting of 28 statements with a Likert scale response and 7 essay questions. The results of data analysis show that students with high belief categories tend to understand the characteristics of contextual mathematical problems and have a description of the steps to solve them, students with moderate belief categories tend to have a correct picture of the definition of contextual mathematical problems but are aware of the difficulties they will face, and students with low belief categories tend not to understand the characteristics of contextual mathematical problems.